UJI AKTIVITAS ANTIBAKTERI ISOLAT Actinomycetes TERHADAP BAKTERI Staphylococcus sp. DAN Streptococcus sp. : Tinjauan Systematic Review - Doraamanda, (2023)
Skin disease caused by bacteria, such as Staphylococcus sp. and Streptococcus sp. which can cause skin infections due to injuries. Several types of Staphylococcus sp. bacteria are normal flora that reside on the skin but can become pathogens that cause diseases such as Staphylococcal Scalded Skin Syndrome. Streptococcus pyogenes, Streptococcus group β hemolysis bacteria can cause skin diseases such as cellulitis, impetigo, and others. The purpose of this study was to determine the antibacterial activity of Actinomycetes isolates against Staphylococcus sp. and Streptococcus sp. as an alternative to antibacterial use. Methods: Systematic Review by conducting a literature search using PubMed, Ebsco, National Library of Indonesia E-Resource. Literature discussing Actinomycetes, Staphylococcus sp. and Streptococcus sp. Results: Based on the 8 journals, 4 journals were obtained with the dependent variable Staphylococcus and the independent variable Actinomycetes with different strains or species and the next 4 journals with the dependent variable Streptococcus and the independent variable Actinomycetes by means of extraction and different species. Conclusion: Actinomycetes isolates can be an alternative as an antibacterial, especially those caused by Staphylococcus sp. and Streptococcus sp.